Through Their Eyes: Children’s Perspectives on Quality in Early Childhood Education - Maryanne Theobald; Chrystal Whiteford; Amanda McFadden (Education Sciences, 2025)
The quality of children’s early childhood education (ECE) experiences significantly impacts their long-term outcomes and wellbeing. While extensive research has explored quality from the perspectives of adult stakeholders, including educators and authorities, there remains a paucity of studies prioritizing the viewpoint of children, the main beneficiaries of ECE. This study sought to address this gap by investigating children’s preschool experiences at an Australian inner-city preschool center. Using child-friendly interview techniques, researchers engaged 32 children aged 3–4 years in discussions about their likes, dislikes, and desired changes in their preschool settings. Open-ended questions such as “What do you love about preschool?” and “What do you think makes a good preschool?” were used to encourage reflection and storytelling. To complement verbal responses, children were invited to illustrate their thoughts through drawings, offering a visual dimension to their perspectives. Deductive thematic analysis identified eight themes within the dimensions of structural and process quality. The findings highlight the unique and insightful ways young children interpret their experiences, shedding light on aspects of preschool life they value most. By amplifying children’s voices, this study highlights the importance of integrating their perspectives into the design and evaluation of ECE environments, promoting practices that better align with their needs and support their wellbeing.